Retrospective Comparative Study to Assess the Safety and Efficacy of Transradial Arterial Access for Hepatic Tumor Embolizations: A Single Operator Experience - Ramanivas Sundareyan; Salil Karkhanis (The Arab Journal of Interventional Radiology, 2023)
Objectives To assess the efficacy and safety of transradial arterial access (TRA) for hepatic tumor embolizations and compare the outcomes between the TRA and transfemoral arterial access (TFA). Materials and Methods A retrospective analysis of all consecutive hepatic tumor embolization procedures done through TFA or TRA by a single operator from November 2017 to April 2019 was performed. The procedural variables, including fluoroscopy time, radiation dose (reference air kerma [RAK]), conversion and complication rates, and patient preferences were recorded. The primary endpoint was technical success, which was defined as the successful completion of the embolization procedure. Procedural variables including radiation exposure and patient preferences, and complications were analyzed as secondary endpoints. Results Out of 102 procedures in 90 patients, 44 were performed through TFA and the rest by TRA. A technical success rate of 98.2% and a crossover rate of 1.7% were recorded for TRA. There were no major vascular complications and similar rates of minor complications (8.6% for TRA, 2.3% for TFA; P = 0.055), without any clinical sequelae. After the initial learning curve, no significant differences for other procedural variables were noted between the two access sites. Faster ambulation were achieved following TRA (P < 0.055). All 12 patients who underwent repeat TACE after initial TRA chose this again over TFA. Conclusions TRA is safe and effective for hepatic tumor embolization. Its safety and efficacy profile is comparable to that of TFA, with added improved patient comfort and faster ambulation. Advances in Knowledge New catheter options and modifications of the existing techniques as explained in this article proved radial arterial access as a safe and effective alternative in hepatic arterial embolization.